Food insecurity during COVID-19 pandemic amongst migrant households of an urban village in Delhi - Singh, Suraj Prakash; Khokhar, Anita; Das, Aritrik (International Journal Of Community Medicine And Public Health, 2025)
Background: The COVID-19 pandemic and associated lockdowns disrupted economic activities and supply chains, leading to rising prices, widespread unemployment, and increased food insecurity. Migrant households, particularly those residing in overcrowded, unplanned urban settlements and working in the unorganized sector, were among the most vulnerable. Assessing food insecurity in this population is essential to guide targeted interventions and policy responses. Methods: A cross-sectional study was conducted in December 2020, between two lockdowns, among migrant households in Aliganj, an urban village in Delhi. Households that had migrated to the area within the past 365 days were eligible. A total of 96 households were selected using systematic random sampling. Data were collected using a pre-designed, pre-tested, semi-structured, interviewer-administered questionnaire in Hindi, which included the household food insecurity access scale (HFIAS). Data analysis was performed using SPSS version 26 and R software. Results: More than half (55.2%) of the migrant households experienced some level of food insecurity, with 14.6% classified as severely food insecure. Lower household income was significantly associated with higher odds of food insecurity. Other contributing factors included irregular employment and larger household size. Conclusions: Food insecurity was highly prevalent among migrant households in the urban village of Aliganj during the COVID-19 pandemic. These findings highlight the urgent need for social safety nets, food assistance, and targeted policy measures to protect vulnerable migrant populations during crises.